2020
DOI: 10.3390/ijerph17217851
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Weight Retention and Its Determinants in Lebanon and Qatar: Results of the Mother and Infant Nutrition Assessment (MINA) Cohort

Abstract: Excessive Postpartum Weight Retention (PWR) is postulated to increase the risk of adverse health outcomes for mothers and offspring. Using data from the Mother and Infant Nutritional Assessment (MINA) cohort in Lebanon and Qatar, this study aimed to examine PWR and its determinants at 6 months after delivery. Pregnant women (n = 183) were recruited during their first trimester and were followed up through pregnancy and after delivery. During this period, face-to-face interviews as well as extraction from medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…The findings of this study showed that over 80% of women had inadequate GWG, and over 50% of participants retained 5 Kg or more at 2 and 6 months postpartum. Such alarming rates are higher than those reported by the Mother and Infant Nutrition Assessment (MINA) cohort conducted in Lebanon and Qatar (64% had inadequate GWG and 36% retained more than 5 Kg at 6 months postpartum) (51) . Compared with other countries around the world, the mean PPWR at 6 months in the study was also higher than those reported from Taiwan (2.1 Kg) (52) , Malaysia (3.12 Kg) (10) , and the United States of American (3.3 Kg) (53) .…”
Section: Discussionmentioning
confidence: 73%
“…The findings of this study showed that over 80% of women had inadequate GWG, and over 50% of participants retained 5 Kg or more at 2 and 6 months postpartum. Such alarming rates are higher than those reported by the Mother and Infant Nutrition Assessment (MINA) cohort conducted in Lebanon and Qatar (64% had inadequate GWG and 36% retained more than 5 Kg at 6 months postpartum) (51) . Compared with other countries around the world, the mean PPWR at 6 months in the study was also higher than those reported from Taiwan (2.1 Kg) (52) , Malaysia (3.12 Kg) (10) , and the United States of American (3.3 Kg) (53) .…”
Section: Discussionmentioning
confidence: 73%
“…Inadequate GWG was in fact reported to heighten the risk for low birthweight (LBW), preterm births and impaired fetal growth, whereas excess GWG was identified as a risk factor for gestational hypertension, gestational diabetes mellitus, preeclampsia, complicated deliveries, macrosomia (Siega‐Riz et al, 2009) and adverse cardiometabolic profile in the offspring (Gaillard et al, 2015). In addition, a convincing body of evidence shows that excessive GWG in all body mass index (BMI) categories is a strong predictor of post‐partum weight retention, which itself is associated with increased risk of adverse health outcomes in subsequent pregnancies including hypertension, diabetes and stillbirth (Nasreddine et al, 2020). In Lebanon, a previous cohort study conducted by our group showed that only 33.9% of pregnant women fell within the adequate GWG range based on the IOM guidelines, whereas 21.3% and 44.9% had inadequate or excessive GWG, respectively (Abdulmalik et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In Lebanon, a previous cohort study conducted by our group showed that only 33.9% of pregnant women fell within the adequate GWG range based on the IOM guidelines, whereas 21.3% and 44.9% had inadequate or excessive GWG, respectively (Abdulmalik et al, 2019). Excessive GWG was also shown to be an independent predictor of post‐partum weight retention in Lebanese women (Nasreddine et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 13 papers are published in this Special Issue entitled "Maternal and Early-Life Nutrition and Health", and the topics include maternal nutrition behaviors [1][2][3][4] and maternal nutrition imbalances, such as maternal high-fat diets [5], maternal high-fructose diets [6], maternal obesity [7], and maternal iron deficiency [8]. Three articles investigated different factors in breastfeeding [9][10][11].…”
mentioning
confidence: 99%